Ancestral knowledge about the use of flora and fauna in the indigenous community Tikuna from Cushillo Cocha, border with Peru-Colombia-Brazil - Rengifo-Salgado, Elsa (2017)
In the present study, ancestral indigenous knowledge (ethno-knowledge) of the indigenous community “Tikuna from Cushillo Cocha” is reported. The community is located in the province of Ramón Castilla, northeast of Loreto Region, Peru. Data was collected through participatory workshops, interviews and biological expeditions in order to collect plant species, observe animals and identify them in situ, always accompanied by local people considered them with experience and knowledge of their territory. A total of 247 species of flora and fauna were registered. In ethnobotany, 101 species were identified, grouped in seven categories of assigned uses by locals, being food and medicinal categories the most representative. For the case of ethnozoology, 146 species were identified, which are used in six categories, being food and pet categories the most relevant. It was evidenced that the forest is the main source for food, medical supplies, handicrafts, animals as pets to be sold and plants as ornamental, all these with important acceptance by the indigenous population.